IRX3 Overexpression Enhances Ucp1 Expression In Vivo - Zhang, Zhiyin; Wu, Qihan; He, Yang; Lu, Peng; Li, Danjie; Yang, Minglan; Gu, Weiqiong; Liu, Ruixin; Hong, Jie; Wang, Jiqiu (Frontiers in Endocrinology, 2021)
Objective: The Iroquois homeobox 3 (IRX3) gene was recently reported to be a functional downstream target of a common polymorphism in the FTO gene, which encodes an obesity-associated protein; however, the role of IRX3 in energy expenditure remains unclear. Studies have revealed that the overexpression of a dominant–negative form of IRX3 in the mouse hypothalamus and adipose tissue promoted energy expenditure by enhancing brown/browning activities. Meanwhile, we and others recently demonstrated that IRX3 knockdown impaired the browning program of primary preadipocytes in vitro. In this study, we aimed to further clarify the effects of overexpressing human IRX3 (hIRX3) on brown/beige adipose tissues in vivo. Methods: Brown/beige adipocyte-specific hIRX3-overexpressing mice were generated and the browning program of white adipose tissues was induced by both chronic cold stimulation and CL316,243 injection. Body weight, fat mass, lean mass, and energy expenditure were measured, while morphological changes and the expression of thermogenesis-related genes in adipose tissue were analyzed. Moreover, the browning capacity of primary preadipocytes derived from hIRX3-overexpressing mice was assessed. RNA sequencing was also employed to investigate the effect of hIRX3 on the expression of thermogenesis-related genes. Results: hIRX3 overexpression in embryonic brown/beige adipose tissues (Rosa26hIRX3;Ucp1-Cre) led to increased energy expenditure, decreased fat mass, and a lean body phenotype. After acute cold exposure or CL316,243 stimulation, white hIRX3-overexpressing mice showed an increase in Ucp1 expression. Consistent with this, induced hIRX3 overexpression in adult mice (Rosa26hIRX3;Ucp1-CreERT2) also promoted a moderate increase in Ucp1 expression. Ex vitro experiments further revealed that hIRX3 overexpression induced by Ucp1-driven Cre recombinase activity upregulated brown/beige adipocytes Ucp1 expression and oxygen consumption rate (OCR) . RNA sequencing analyses indicated that hIRX3 overexpression in brown adipocytes enhanced brown fat cell differentiation, glycolysis, and gluconeogenesis. Conclusion: Consistent with the in vitro findings, brown/beige adipocyte-specific overexpression of hIRX3 promoted Ucp1 expression and thermogenesis, while reducing fat mass.